2002
DOI: 10.1007/s10029-002-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Day surgery for laparoscopic repair of abdominal wall hernias

Abstract: Laparoscopic repair of abdominal wall hernias is still a controversial and nongeneralized therapeutic option. The aim of this paper is to evaluate the results of laparoscopic surgery on abdominal wall hernias at a day-surgery unit and to describe our procedure protocol. Prospective analysis of 300 patients undergoing laparoscopic surgery for abdominal wall hernias was conducted: 260 preperitoneal and 40 intraperitoneal. The patients' clinical features, hernia type, intraoperative and postoperative complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…[95][96][97] Morbidity is less than with open repair and the recurrence rate in recent studies of primary Spigelian hernia after TEP herniorrhaphy was 0 per cent. 31,52,53,[94][95][96][97] Similarly, proponents of TAPP claim shorter hospital stays and decreased morbidity compared with open operation. TAPP repair of a Spigelian hernia may be most applicable in patients with other pathology such as inguinal or ventral hernias that could be repaired concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…[95][96][97] Morbidity is less than with open repair and the recurrence rate in recent studies of primary Spigelian hernia after TEP herniorrhaphy was 0 per cent. 31,52,53,[94][95][96][97] Similarly, proponents of TAPP claim shorter hospital stays and decreased morbidity compared with open operation. TAPP repair of a Spigelian hernia may be most applicable in patients with other pathology such as inguinal or ventral hernias that could be repaired concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were seen in the study done by Lau et al in which 100% cases were discharged on the same day. 15,16 Witten becher et al also found similar results in favour of TEP. 17 This can be explained by the factor that the laparoscopic surgery has minimal invasion and lesser degree of surgical incisions and hence these cases need lesser hospital stay and care, hence discharged earlier.…”
Section: Discussionmentioning
confidence: 68%
“…Once laparoscopic approach was shown to be efficient for ventral hernia repair, the technique was developed and extended to other defects of the abdominal wall [8,10,11,13]. Lumbar hernias are rare and not well understood.…”
Section: Discussionmentioning
confidence: 99%